Uruguay : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper examines the dimensions in which Uruguay's financial development is lagging, and the benefits that might accrue if obstacles to development in these areas were removed. The analysis focuses on the frictions affecting firms' access to credit, corporate credit deepening, and the efficiency of financial intermediation in Uruguay, and quantifies the potential economic benefits of relaxing these constraints, with implications for firms and households alike. The paper also lays out the basic premises of the model, together with some facts to illustrate different elements of it. The paper presents the results of the calibration and comparative statics exercise. The last section concludes with a discussion of measures that have been taken by the Uruguayan authorities recently, which may alleviate some of the constraints emphasized in the model. The challenge is to implement these measures in a way that maximizes their effectiveness. This may require communication campaigns targeting the youth, elderly and low-income segments of the population, to ensure the widest reach, particularly outside Montevideo.